(untitled) (ModaPalavra e-periódico, 2020)
The present study aims to identify the context of production of Renaissance and Irish lace in the artisan associations of São João do Tigre, Paraíba and Divina Pastora, in Sergipe. The qualitative and descriptive research was used and the data collection was done using bibliographical and field research, with the application of a semi-structured questionnaire. The research sample is made up of four entities, two associations and one cooperative that produce Renaissance Income in the city of São João do Tigre, in the State of Paraíba, and an association that produces Irish Income in the city of Divina Pastora, in the State of Sergipe. Through the study, it was noticed that each entity has a form of organization and that its main challenges refer to the preservation of the techniques and the commercialization of the products.